Lymphocyte subpopulations and Treg cells in dogs with atopic dermatitis receiving ciclosporin therapy: a prospective study. Issue 1 (11th December 2015) - Beccati, Massimo; Martini, Valeria; Comazzi, Stefano; Fanton, Natalia; Cornegliani, Luisa
Abstract : Background: Canine atopic dermatitis (CAD) is a chronic dermatological disease partly due to dysregulation of the immune system. Inappropriate activation of CD4 + lymphocytes could favour and promote the allergic response. An inadequate activation system of regulatory T cells (Tregs) is suspected to be a key immunological feature of the allergic response in atopic dogs. Hypothesis/Objectives: To evaluate the difference in the CD4/CD8 lymphocyte ratio and the percentage of Tregs in healthy dogs, in a breed predisposed to CAD, and in dogs affected by CAD before and during therapy with ciclosporin (CsA). Additionally to assess the improvement in pruritus and skin lesions during therapy with CsA, and to compare this with CD4/CD8/Treg values. Animals: Ten atopic dogs of different breed, sex and age, ten healthy dogs and ten English bulldogs were included. Methods: Peripheral blood from all dogs was tested using flow cytometry to assess the CD4/CD8 ratio and percentage of Tregs. For atopic dogs, sampling was repeated after 30 and 90 days of therapy with CsA. Results: The CD4/CD8 ratio was not significantly different between the three groups. The Treg percentage was higher, but not statistically significant, in atopic dogs compared with controls. Therapy with CsA led to clinical improvement; it was not associated with statistically significant differences in haematological variables. Conclusion and clinical importance: This study suggests that Tregs may be involved in the pathogenesis of CAD and that ciclosporin therapy does not affect the circulating lymphocyte subpopulations Abstract : Background –Canine atopic dermatitis (CAD) is a chronic dermatologic disease partly due to dysregulation of the immune system.Inappropriate activation of CD4 + lymphocytes could favour and promote the allergic response. An inadequate activation system of regulatory T cells (Tregs) is suspected to be a key immunologic feature of the allergic response in atopic dogs.Hypothesis/Objectives –To evaluate the difference in the CD4/CD8 lymphocyte ratio and the percentage of Tregs in healthy dogs, in a breed predisposed to CAD and in dogs affected by CAD before and during therapy with ciclosporin (CsA), and to assess the improvement in pruritus and skin lesions during therapy with CsA and to compare this with CD4/CD8/Treg values.Conclusion and clinical importance –This study suggests that Tregs may be involved in the pathogenesis of CAD and that ciclosporin therapy does not affect the circulating lymphocyte subpopulations.